2020
DOI: 10.1007/s00586-020-06392-w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty as treatment of malignant vertebral lesions: a systematic review and GRADE evaluation resulting in a Danish national clinical guideline

Abstract: Purpose To summarize the recommendations from the national clinical guideline published by the Danish Health Authority, regarding cemental augmentation as treatment for painful vertebral lesions, in patients with malignant disease. Methods A multidisciplinary working group formulated recommendations based on the GRADE approach. Results Two of the questions were based on randomized studies and one on professional consensus. The guideline recommends cemental augmentation for painful vertebral lesions in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A retrospective analysis, with 18 myeloma patients who underwent vertebroplasty prior to autologous stem cell transplant showed that vertebroplasty could be done without affecting peripheral blood stem cell collection and transplant [109]. The current recommendation in myeloma associated vertebral collapse is to consider vertebral augmentation if it causes moderate or severe pain, and particularly if it affects mobilization [110] This is supported by a recently published national guideline based on the GRADE-approach [111] recommending vertebral augmentation as treatment in patients with painful vertebral lesions and malignant hematologic disease [112].…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…A retrospective analysis, with 18 myeloma patients who underwent vertebroplasty prior to autologous stem cell transplant showed that vertebroplasty could be done without affecting peripheral blood stem cell collection and transplant [109]. The current recommendation in myeloma associated vertebral collapse is to consider vertebral augmentation if it causes moderate or severe pain, and particularly if it affects mobilization [110] This is supported by a recently published national guideline based on the GRADE-approach [111] recommending vertebral augmentation as treatment in patients with painful vertebral lesions and malignant hematologic disease [112].…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…Additionally, the cement consolidates and stabilizes fractured fragments and prevents further vertebral body collapse 7 . Vertebroplasty is recommended by several adult medical societies for the palliative treatment of painful oncologic fractures or weakened vertebral bodies secondary to neoplasms, with a reported clinical success of 92% and major complication rate < 1% [24][25][26][27][28][29] . Vertebroplasty can be performed under conscious sedation or general anesthesia and takes approximately 15-30 minutes, with an increment of 5-15 minutes for any additional vertebral level treated 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cement consolidates and stabilizes fractured fragments and prevents further vertebral body collapse 16 . Vertebroplasty is recommended by several adult medical societies for the palliative treatment of painful oncologic fractures or weakened vertebral bodies secondary to neoplasms, with a reported clinical success of 92% and major complication rate <1% 17–22 …”
Section: Discussionmentioning
confidence: 99%
“…16 Vertebroplasty is recommended by several adult medical societies for the palliative treatment of painful oncologic fractures or weakened vertebral bodies secondary to neoplasms, with a reported clinical success of 92% and major complication rate <1%. [17][18][19][20][21][22] The procedure is associated with significant pain reduction and increase in the level of function, with sustained long-term benefit.…”
Section: Percutaneous Vertebroplasty Injects Polymethyl Methacrylatementioning
confidence: 99%